2013
DOI: 10.1007/s12149-013-0697-5
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic late-onset sialadenitis after radioiodine therapy in thyroid cancer

Abstract: Symptomatic late-onset sialadenitis occurred at an incidence of 10.2 %, and salivary gland function was affected in both parotids in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…This may be explained by the relative radiosensitivity of the serous cells in the parotid glands. However, the mucinous tissue of the submandibular glands might have contributed to a radioprotective effect [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the relative radiosensitivity of the serous cells in the parotid glands. However, the mucinous tissue of the submandibular glands might have contributed to a radioprotective effect [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Swelling and pain of salivary gland are the most common symptoms in early sialadenitis while xerostomia is the most prominent symptom in chromic sialadenitis after RAI therapy. An YS et al [5] found the ratio of late-phase (mean 338 days) symptomatic sialadenitis as 10% after RAI therapy. Early sialadenitis occurs in a short time after RAI theraphy with swelling and pain symptoms and usual-ly subsides over a few days spontane-ously.…”
Section: Discussionmentioning
confidence: 99%
“…Parotid gland involve-ment is observed more frequently as it contains more serous cells than mucous cells [7]. Moreover, high mucin secre-tion in the submandibular glands pro-tect these glands from exposure to radi-ation [5]. Interestingly, although its rea-son has not been fully explained yet, there are studies reporting that the right parotid gland is affected more [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenously administered 99m Tc-pertechnetate gradually accumulates in the salivary glands over 20 min postadministration and is then excreted as saliva production is enhanced. This type of scintigraphy yields semiquantitative data on uptake ratios and %excretion values [16][17][18]. However, no reliable method has yet been developed to predict functional impairment of salivary glands at the time of 131 I ablation therapy.…”
Section: Introductionmentioning
confidence: 99%